Revealing RB1 loss in an emerging entity: report of two cases of PRRX1-rearranged mesenchymal tumours - Cordier, Fleur; Fadaei, Sharareh; Ferdinande, Liesbeth; Dochy, Frederick; Vanwalleghem, Lieve; Van Den Bossche, Karolien; Loontiens, Siebe; Van der Meulen, Joni; Van Roy, Nadine; Van Dorpe, Jo; Creytens, David (Journal of clinical pathology, 2025)
Aims PRRX1-rearranged mesenchymal tumours are a recently identified and rare subgroup of soft tissue neoplasms with distinct morphological features and genetic alterations. This study aims to further investigate the immunohistochemical profile and underlying genetic alterations in these tumours in order to get more insight on their underlying biology and the unique profile of these tumours.MethodsTwo new molecular confirmed cases of PRRX1-rearranged mesenchymal tumours were thoroughly studied with immunohistochemical stainings (RB1, CD34, ALK and pan-TRK), fluorescence in situ hybridisation (FISH) RB1/13q12 and RNA-based next-generation sequencing.ResultsBoth cases exhibited typical morphological and molecular features, confirming the diagnosis of PRRX1-rearranged mesenchymal tumours. Immunohistochemistry revealed RB1 loss in both cases, which was subsequently confirmed through FISH analysis. Additionally, one case showed focal positivity for CD34, ALK and pan-TRK on immunohistochemistry.ConclusionsWe identified loss of RB1 in two cases of PRRX1-rearranged mesenchymal tumours. This could suggest a potential association with RB1-deficient soft tissue tumours, although further research is necessary. Furthermore, the finding of focal positivity for CD34, ALK and pan-TRK on immunohistochemistry enriches the immunohistochemical profile of these tumours.